Microfluidic flow simulation in multi-geometry square microchannels - Taniselass, Steven (School of Microelectronic Engineering, 2011)
The purpose of this research is to investigate the dynamics of water coupled with its behavior characteristic in multi-geometry square microchannels, particularly in smooth straight, obstructed straight, miter bend and curve 90 microchannels. This is because, in photonics niche, planar waveguides are preferably square in order to obtain the desired single mode electromagnetic cross-section distribution. In this case, square microchannels with hydraulic diameter of about 5 Vm (for single mode at 670 nm) have been used to understand the flow behavior in this research.